Understanding The Intention to Use PLN Mobile Application: The Moderated Mediation Analysis - Aidil Adha; Vidyarini Dwita; Tika Rahma Yani Siregar (Jurnal Aplikasi Bisnis dan Manajemen, 2025)
Background: Mobile technology serves as a strategic element that enhances consumer experience and strengthens interactions between consumers and service providers. Prior studies indicate that such technology facilitates user customization, simplifies information retrieval, and streamlines customer-company interactions. A thorough understanding of user intention toward the PLN Mobile application is critical for reinforcing customer relationships, boosting loyalty and satisfaction, and generating revenue growth through value-added services.Purpose: This study aims to examine the influence of perceived usefulness and technology acceptance on the intention to use the PLN Mobile application. Additionally, the study also investigates the mediating role of attitude toward use and the moderating role of subjective norm in influencing the intention to use the PLN Mobile application.Design/methodology/approach: This study employs a quantitative survey-based design with a sample of 260 employees customers of PLN UP3 Padangsidempuan. A purposive sampling approach was adopted for participant selection. The data collection was conducted in 2024. The data were analyzed using structural equation modeling with partial least squares (SEM PLS)Findings/Results: The results of the study demonstrate that both perceived usefulness and technology acceptance have a positive and significant impact on the intention to utilize the PLN Mobile application. Additionally, the study reveals that attitude toward use acts as a mediator in the relationship between perceived usefulness, technology acceptance, and intention to use. Moreover, the effect of perceived usefulness and technology acceptance on the intention to use the PLN Mobile application was moderated by subjective norm. The mediating role of attitude toward use underscores the necessity for extending the Technology Acceptance Model (TAM) by incorporating psychological variables to achieve a more holistic understanding of user intention. Furthermore, the moderating effect of subjective norm highlights the critical influence of social factors in technology usage.Conclusion: Technology acceptance and perceived usefulness significantly influence the intention to use the PLN Mobile application. Positive attitudes toward the application, formed by perceived usefulness and technology acceptance, further enhance the intention to use. Additionally, subjective norm play a crucial role in motivating individuals to use the application.Originality/value (State of the art): This study examines the role of technology acceptance as a single construct and integrates the TPB and TAM models to provide a theoretical framework. Keywords: attutude toward use, intention to use, perceived usefulness, subjective norm, technology acceptance